DAMPAK USAHA MIKRO KECIL MENENGAH(UMKM) TERHADAP KESEJAHTERAAN MASYARAKAT (STUDI KASUS UMKM KULINER KECAMATAN PADANG TUALANG, KABUPATEN LANGKAT) - fauja, zalika (JURNAL EKONOMI SYARIAH, 2022)
In terms of meeting the needs of life to be prosperous, people who have the ability and expertise open up business opportunities for the community. Efforts made to meet the needs of life include Micro, Small and Medium Enterprises (MSMEs). This research was conducted aiming to see the impact of MSMEs on the welfare of the community. The study was conducted with a descriptive qualitative approach, researchers conducted research in culinary SMEs in the Padang Tualang sub-district, Langkat Regency. The results obtained from this study say that MSMEs have a positive impact on people's welfare in terms of health, education, income, housing and communicationÂ